Early initiated postoperative rehabilitation reduces fatigue in patients with operable lung cancer: A randomized trial. (December 2018) - Quist, Morten; Sommer, Maja Schick; Vibe-Petersen, Jette; Stærkind, Maja Bohlbro; Langer, Seppo W.; Larsen, Klaus Richter; Trier, Karen; Christensen, Merete; Clementsen, Paul F.; Missel, Malene; Henriksen, Carsten; Christensen, Karl Bang; et al.
Highlights: Effect of exercise postoperative rehabilitation with operable lung cancer. To reduce fatigue patients should be recommended to initiate early exercise programs. No differences between the groups after 26 weeks. Abstract: Introduction: Little is known about the optimal amount and timing of exercise strain in concern of the operation wound and with regard improvement of physical function and quality of life (QOL) after surgery for lung cancer. On this background, we decided to investigate the effect of early vs. late initiated postoperative rehabilitation in patients with operable lung cancer on exercise capacity, functional capacity, muscle strength, and QOL. Methods: The study was designed as a two-armed randomized controlled trial with randomization to either early initiated postoperative rehabilitation (14 days after surgery (ERG)) or a control arm with late initiated postoperative rehabilitation (14 weeks after surgery (LRG)). The primary endpoint was a change in maximum oxygen consumption (VO2peak) from baseline to post intervention 26 weeks following lung resection. Fatigue was measured with EORTC QLQ C30 LC13. Results: From April 2013 to June 2016, 582 patients with operable NSCLC were screened for eligibility. With 119 patients randomized in the early rehabilitation group (ERG) and 116 randomized to late rehabilitation group (LRG). There was no significant difference from baseline to 26 weeks between ERG and LRG (p = 0.926). There was a significant difference from baseline to 14 weeks between groups (p = 0.0018). There was a significant difference from 14 weeks to 26 weeks between the two groups (p < 0.001). We found no significant differences in QOL but we found a significant difference between ERG and LRG from baseline to 14 weeks in fatigue level in favour of ERG. Conclusion: This is the first randomized controlled trial to investigate the effects of early vs. late initiated postoperative rehabilitation in patients with lung cancer. There is no difference in the commencement (early vs. late) of a postoperative exercise program for patients with lung cancer on exercise capacity. But to reduce fatigue patients should be recommended to initiate early exercise programs.